Evaluation of Grewia optiva fiber as a sustainable and high-performance reinforcement material for composite applications - Thandavamoorthy Raja; Yuvarajan Devarajan; Sundram Vickram (Results in Engineering)
This study demonstrates the potential of novel fiber extracted from the Grewia optiva plant as a sustainable and high-performance reinforcement material for composites. The fiber exhibited strong antimicrobial properties, with inhibition zones of 27 mm and 25 mm against Aeromonas for high and low extract concentrations, respectively. It showed excellent thermal stability, with decomposition temperatures ranging from 366.17 °C to 470.46 °C, making it ideal for flame-retardant applications. Mechanical testing revealed significant tensile strength (11.8 MPa) and Young's modulus (5.4 GPa), highlighting its suitability for lightweight and durable composites. Furthermore, its natural UV resistance, indicated by a peak at 280 nm, enhances its performance in outdoor applications. These results reveals the potential of Grewia optiva fiber as a sustainable, eco-friendly alternative for advanced composite materials, addressing key environmental and performance demands.